PICES Press, Vol. 25, No. 1, Winter 2017 - North Pacific Marine Science Organization (PICES) (North Pacific Marine Science Organization (PICES), 2017)
PICES science in 2016: A note from the Science Board Chair (pp. 1-8); 2016 PICES awards (pp. 9-12); PICES calendar of events (pp. 13-13); Impressions of PICES from old friends (pp. 14-17); S-CCME Workshop W5, “Modeling effects of climate change on fish and fisheries (pp. 18-22); In memoriam: Professor Emeritus Paul J. Harrison (pp. 23-23); Workshop W9, “The role of the northern Bering Sea in modulating arctic environments” (pp. 24); A symposium to mark the 60th anniversary of Station Papa/Line P (pp. 28-29); To the interface and beyond: Results and legacy of SCOR Working Group 140 (pp. 30-31); Webcam monitoring and modeling of Japanese tsunami marine debris (pp. 32-35); Mapping patterns of marine debris in the main Hawaiian Islands using aerial imagery and spatial analysis (pp. 36-39); New leadership in PICES (pp. 40-44); PICES interns (pp. 45-45); The Bering Sea: Current status and recent trends (pp. 46-49); The state of the western North Pacific during the 2016 warm season (pp. 50-51)